2015
DOI: 10.9738/intsurg-d-14-00269.1
|View full text |Cite
|
Sign up to set email alerts
|

Intestinal Obstruction Caused by Persimmon Bezoar: A Case Report

Abstract: Owing to their rare occurrence, persimmon bezoars are often overlooked as a cause of small bowel obstruction. We herein report a small bowel obstruction in a 67-year-old Japanese female who regularly consumed persimmons in autumn. The patient presented to our hospital with typical complaints of abdominal distension with pain for 2 days. Based on the patient's history of a cesarean section 34 years ago, we initially diagnosed her with small bowel obstruction resulting from adhesions and placed an ileus tube. At… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 19 publications
0
9
0
Order By: Relevance
“…The first choice of treatment for bezoars is removal by endoscopy or a surgical procedure [1]. In our case, however, a surgical procedure might have been difficult because the bezoar was located in the reconstructed gastric conduit through the posterior sternum.…”
Section: Discussionmentioning
confidence: 92%
See 2 more Smart Citations
“…The first choice of treatment for bezoars is removal by endoscopy or a surgical procedure [1]. In our case, however, a surgical procedure might have been difficult because the bezoar was located in the reconstructed gastric conduit through the posterior sternum.…”
Section: Discussionmentioning
confidence: 92%
“…Intestinal obstruction is the most prevalent complication of bezoar formation [1]. In one report, CT scans were useful to accurately diagnose intestinal obstruction caused by bezoars in more than 70% of the cases [6].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…There have been few reports on the endoscopic treatment of small intestinal obstruction due to a single bezoar ( 2 , 3 ). In contrast, it has been reported that surgical intervention is inevitable for the treatment of small intestinal obstruction with multiple bezoars ( 1 , 10 ). Certainly, there have been cases of immobile small bowel bezoars with impaction, massive bleeding, or perforation.…”
Section: Discussionmentioning
confidence: 99%
“…Tannins exist in numerous other organic materials, including plants, woods, and seeds. When large amounts of persimmons are achieved, tannins may interact with gastric acid and polymerize fibers to form a hard phytobezoar [5]. Persimmon phytobezoars are more difficult to break up into pieces, compared with other phytobezoars.…”
Section: Introductionmentioning
confidence: 99%